2019
DOI: 10.1111/jfbc.13045
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomic analysis of hen egg yolk plasma proteins during embryonic development

Abstract: Avian egg yolk provides essential nutrients and physiological support for the developing embryo. To reveal the dynamics of yolk proteins during the entire period of incubation, we analyzed the alterations of egg yolk plasma proteins at different times during incubation (day 0, 7, 14, and 18). Day 14 (D14) of incubation was considered as the key point on the alteration of egg yolk proteins according to the SDS‐PAGE analysis. The two‐dimensional electrophoresis‐based comparative proteomic analysis was conducted,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 40 publications
2
11
0
Order By: Relevance
“…Specifically, nine eggs were selected as the experimental samples at D0 and D12 of incubation. Then selected experimental fertilized eggs were stored under −80 °C for 2 h, removing the eggshell, eggshell membrane, as well as yolk membrane with a knife, leaving the chicken egg white and egg yolk mixtures (CEM) as a whole and as experimental samples . Finally, the CEM samples were frozen at −80 °C for further experiment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, nine eggs were selected as the experimental samples at D0 and D12 of incubation. Then selected experimental fertilized eggs were stored under −80 °C for 2 h, removing the eggshell, eggshell membrane, as well as yolk membrane with a knife, leaving the chicken egg white and egg yolk mixtures (CEM) as a whole and as experimental samples . Finally, the CEM samples were frozen at −80 °C for further experiment.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, to study the changes of egg protein phosphorylation status during incubation and the effects of these changes on chicken embryonic development, a comparative quantitative phosphoproteomic study based on mass spectrometry was performed to analyze the fertilized chicken egg white and yolk mixtures (CEM) during incubation (D0 and D12 of incubation) using TMT labeling in combination with an immobilized metal affinity chromatography (IMAC) enrichment strategy. D12 was chosen as a key point due to the results from our former studies 19,20 as well as those from other studies; for example, Rehault-Godbert et al detected that the most dramatic changes in egg yolk proteins were observed at day 12, which was defined as the end of embryo completion. 4 Our study helps us to further understand the biological functions of egg phosphoproteins during incubation and lays a solid foundation for future research of chicken embryonic development.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Phosphorylation of OTF not only enhanced its antimicrobial activity against Staphylococcus aureus, Bacillus subtilis and Escherichia coli (Huang et al., 2013), but also improved its antioxidant activity (Mine, Li‐Chan, & Jiang, 2011). Our recent study reported that OTF also helps to defend the embryo against pathogens during embryogenesis (Meng et al, 2019). As a result, it can be postulated that due to the key role of phosphorylation in enhancing antibacterial activity of OTF, the increased phosphorylation of S525 in DEW might promote its antibacterial activity to defend against the attacks by Gram‐positive bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the relative abundance of lipids of free fatty acid (FA) (22:4), FA(22:5), and FA(22:6) declined after day 13. In addition, the extracellular fatty acid-binding protein, which plays a role in uptaking long-chain fatty acids (carbon number >12) was upregulated on day 13 in the egg yolk during the chick embryogenesis . These decreased long-chain fatty acids may be transported from YS to the embryo by the extracellular fatty acid-binding protein and meet specific neurodevelopmental needs.…”
Section: Discussionmentioning
confidence: 99%